Silver sulfide-based plastic thermoelectric material and preparation method and application thereof
By reducing the electronegativity of anion position and introducing silver vacancy, the carrier concentration of silver sulfide-based plastic thermoelectric materials is optimized, and the problem of insufficient thermoelectric performance in the prior art is solved, and the material is efficient thermoelectric conversion and good plastic deformation capabilities are achieved, which is suitable for power supply of flexible electronic devices.
Patent Information
- Application Number
- CN202510394555.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-08-05
AI Technical Summary
The existing silver sulfide-based plastic thermoelectric materials have not been optimized in the optimization of carrier concentration, resulting in their thermoelectric properties being inferior to that of classic inorganic plastic thermoelectric materials, and the structural stability and plastic deformation ability of the material are insufficient.
By reducing the electronegativity of anion position and introducing silver vacancy strategies, the carrier concentration of Ag6SSeTe material is optimized, and the preparation processes of ball milling, cold pressing and annealing are used to control material components, improve thermoelectric properties and maintain the structural stability of the material.
The thermoelectric properties of silver sulfide-based plastic thermoelectric materials have been significantly improved, and the room temperature thermoelectric value is increased by 6 times, while maintaining good plastic deformation ability and structural stability, which is suitable for power supply of flexible electronic devices.
Smart Images

Figure CN120435216A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermoelectric materials, and in particular to a silver sulfide-based plastic thermoelectric material and a preparation method and application thereof. Background Art
[0002] Plastic thermoelectric devices, based on the Seebeck effect, convert the temperature difference between the human body and the surrounding environment into electrical energy to power flexible electronic devices. They can also better conform to the surface of the heat source, improving energy conversion efficiency. Compared to traditional chemical batteries, they offer greater portability, higher reliability, and longer lifespan, making them a promising energy supply solution for flexible electronics.
[0003] Excellent plastic thermoelectric materials must possess both excellent thermoelectric properties to achieve high thermoelectric conversion efficiency and good plastic deformation to conform to curved heat source surfaces. Based on these requirements, silver sulfide semiconductor materials have become an emerging research direction in the field of inorganic plastic thermoelectrics due to their metal-like ductility and carrier mobility comparable to classic inorganic thermoelectric materials.
[0004] Intrinsic silver sulfide semiconductor materials (pure silver sulfide semiconductor materials) have extremely low carrier concentrations, resulting in room-temperature power factors and thermoelectric figures of merit far below those of classical inorganic thermoelectric materials. Previous studies have significantly optimized the carrier concentration by solid-dissolving selenium and tellurium in place of sulfur in silver sulfide, but these efforts have failed to achieve optimal carrier concentration. Consequently, the thermoelectric performance of current silver sulfide-based plastic thermoelectric materials is significantly inferior to that of classical inorganic plastic thermoelectric materials.
[0005] CN116835536A discloses a silver-based chalcogenide thermoelectric material and its preparation method and application. The chemical formula of the silver-based chalcogenide thermoelectric material is Ag 2-δ S x Se y Te z , where δ = 0 ~ 0.05, x = 0.25 ~ 0.8, y = 0 ~ 0.5, z = 0.3 ~ 0.7, and x + y + z = 1, silver-based chalcogenide thermoelectric material is a cubic structure quaternary compound with a special body-centered cubic crystal structure. It has excellent plasticity and deformation ability while ensuring thermoelectric performance. However, the Ag disclosed in the patent 1.98 S 1 / 3 Se 1 / 3 Te 1 / 3 The thermoelectric performance of the material is still significantly inferior to that of traditional classic inorganic plastic thermoelectric materials. Summary of the Invention
[0006] The purpose of the present invention is to provide a silver sulfide-based plastic thermoelectric material and its preparation method and application in order to solve the above problems. The strategy of reducing the electronegativity of the anion position and introducing silver vacancies is combined to achieve the optimization of the carrier concentration of the Ag6SSeTe material, so that its thermoelectric performance is significantly improved while maintaining the good mechanical properties and structural stability of the material. A high-performance silver sulfide-based plastic thermoelectric material and its preparation method and application are provided. The thermoelectric performance of the prepared sample is improved by 6 times that of the initial sample (Ag6SSeTe), with excellent room temperature thermoelectric figure of merit, while maintaining good plastic deformation ability.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] The first object of the present invention is to provide a silver sulfide-based plastic thermoelectric material, wherein the structural chemical formula of the silver sulfide-based plastic thermoelectric material is Ag 6-y SSe 1-x Te 1+x , where 0 <x<0.50,0≤y<0.03。
[0009] More preferably, 0 <x<0.50,0<y<0.03。
[0010] Further, x=0.10, 0.20, 0.30, 0.40.
[0011] Furthermore, y=0.02.
[0012] More preferably, x=0.40, y=0.02.
[0013] When x≥0.50, Ag 6-y SSe 1-x Te 1+x Because the Te element exceeds the solid solubility limit, the Ag2Te second phase will precipitate, which will cause the composition of the base material to change, reducing the repeatability of material preparation and performance stability.
[0014] Furthermore, the cubic phase structure of the silver sulfide-based plastic thermoelectric material remains stable in the temperature range of 300-450K; the room temperature thermoelectric figure of merit of the silver sulfide-based plastic thermoelectric material is 0.60-0.70; and under vertical compression, the compressive strain of the silver sulfide-based plastic thermoelectric material is 40-50%.
[0015] Further preferably, when x=0.40 and y=0.02, the cubic phase structure of the silver sulfide-based plastic thermoelectric material remains stable in the temperature range of 300-450K, the room temperature thermoelectric figure of merit of the silver sulfide-based plastic thermoelectric material is 0.65, and under vertical compression, the compressive strain of the silver sulfide-based plastic thermoelectric material is 45%.
[0016] The second object of the present invention is to provide a preparation method of a silver sulfide-based plastic thermoelectric material, and the preparation method includes the following steps:
[0017] Step 1: Weighing
[0018] Weigh elemental Ag 6-y SSe 1-x Te 1+x according to the stoichiometric ratio, where 0 < x < 0.50 and 0 ≤ y < 0.03, respectively weigh elemental Ag (silver), elemental S (sulfur), elemental Se (selenium), and elemental Te (tellurium);
[0019] Step 2: Ball milling
[0020] Mix the elemental Ag, elemental S, elemental Se, and elemental Te weighed in Step 1 and perform ball milling to obtain flaky Ag 6- y SSe 1-x Te 1+x alloy;
[0021] Step 3: Cold pressing
[0022] Cold press the flaky Ag 6-y SSe 1-x Te 1+x alloy obtained by ball milling in Step 2 to obtain a dense块状 Ag 6-y SSe 1- x Te 1+x alloy;
[0023] Step 4: Annealing
[0024] Anneal the dense块状 Ag 6-y SSe 1-x Te 1+x alloy obtained in Step 3 in a vacuum to obtain Ag 6-y SSe 1- x Te 1+x plastic thermoelectric material, which is the silver sulfide-based plastic thermoelectric material.
[0025] Further, in Step 1, weigh elemental Ag, elemental S, elemental Se, and elemental Te respectively under an inert atmosphere (such as argon).
[0026] Further, in Step 1, weigh elemental Ag, elemental S, elemental Se, and elemental Te respectively in an argon glove box.
[0027] Further, in Step 2, the process of mixing and performing ball milling is carried out under an inert atmosphere (such as argon).
[0028] Furthermore, in step 2, the mixing and ball milling process is carried out in an argon glove box.
[0029] Furthermore, in step 2, the ball milling specifically includes the following process: adding ball milling beads, sealing the ball milling jar, placing the ball mill in a ball mill for ball milling, and ball milling for 20-30 hours at a rotation speed of 800-1000 rpm.
[0030] Furthermore, in step 2, the ball mill is a high-energy ball mill, the ball milling jar and the ball milling beads are both made of stainless steel, the diameter of the ball milling beads is 8-15 mm, and the number is 3-10.
[0031] Further preferably, in step 2, the diameter of the ball milling beads is 10 mm and the number is 4.
[0032] Further preferably, in step 2, the rotation speed of the ball mill is 875 rpm and the ball milling time is 20 h.
[0033] Furthermore, step 3 specifically includes the following process:
[0034] The Ag flakes obtained by ball milling in step 2 6-y SSe 1-x Te 1+x The alloy is transferred to a cold pressing die, a cold pressing punch is added, and the pressure is increased to 50-70 MPa. The pressure is maintained at room temperature for 20-30 minutes to obtain a dense block of Ag. 6-y SSe 1-x Te 1+x alloy.
[0035] Furthermore, in step 3, the cold pressing mold is a stainless steel cold pressing mold, the inner diameter of the cold pressing mold is 8-15 mm, and the diameter of the cold pressing punch is 7.7-14.7 mm.
[0036] Further preferably, in step 3, the inner diameter of the cold pressing die is 13 mm, and the diameter of the cold pressing punch is 12.7 mm.
[0037] Further preferably, in step 3, the cold pressing pressure is 60 MPa and the holding time is 20 min.
[0038] Furthermore, step 4 specifically includes the following process:
[0039] The dense bulk Ag obtained in step 3 6-y SSe 1-x Te 1+x The alloy was transferred to the infrared rapid annealing furnace cavity, and the infrared rapid annealing furnace cavity was evacuated to a vacuum of 3-5 Pa. The temperature was then raised to 200-300 ° C, kept at this temperature for 10-20 minutes, and then cooled to room temperature in the infrared rapid annealing furnace to obtain Ag.6-y SSe 1-x Te 1+x The plastic thermoelectric material is the silver sulfide-based plastic thermoelectric material.
[0040] Furthermore, in step 4, the heating rate of the infrared rapid annealing furnace is 40-60° C. / min.
[0041] Further preferably, in step 4, the heating rate of the infrared rapid annealing furnace is 50° C. / min, the holding temperature is 250° C., and the holding time is 10 min.
[0042] The third object of the present invention is to provide an application of a silver sulfide-based plastic thermoelectric material, wherein the silver sulfide-based plastic thermoelectric material is used to power room-temperature flexible electronic devices.
[0043] The concept of the present invention is as follows: The research and development concept of the scheme of the present invention is to improve the thermoelectric performance of Ag6SSeTe materials. First, by increasing the content of Te element in the anion position of Ag6SSeTe material, the electronegativity of the anion position is reduced, and then more cation vacancies are introduced to reduce the silver interstitial ions that provide donor energy levels in the material. The reduction of silver interstitial ions helps to reduce the excessive carrier concentration in Ag6SSeTe material, which is beneficial to the improvement of the material power factor and the reduction of electronic thermal conductivity. Since Te element has a solid solubility limit in Ag6SSeTe material. Therefore, in Ag6SSe 0.6 Te 1.4 A small amount of silver vacancies was further introduced on the basis of the material, the purpose of which was to reduce the silver interstitial ions. Benefiting from the combined effect of the reduced electronegativity of the anion position and a small amount of silver vacancies, Ag 5.98 SSe 0.6 Te 1.4 The carrier concentration in the material is optimized. The optimized carrier concentration significantly improves the power factor of the sample while effectively reducing the total thermal conductivity of the material, making Ag 5.98 SSe 0.6 Te 1.4 The material's room-temperature thermoelectric figure of merit reaches 0.65, a six-fold improvement over the unoptimized sample (Ag6SSeTe). Furthermore, to control the volatilization of S, Se, and Te during the sample preparation process, the present invention proposes a preparation process involving ball milling, cold pressing, and annealing, based on the material's inherent plasticity. This process prevents the volatilization of S group elements by avoiding high temperatures during sample synthesis, thereby achieving precise composition control and improving the repeatability of material preparation.
[0044] Compared with the prior art, the present invention has the following characteristics:
[0045] 1) This invention provides a silver sulfide-based plastic thermoelectric material, its preparation method, and its application. This silver sulfide-based plastic thermoelectric material currently offers the best room-temperature thermoelectric performance. This invention combines the strategy of reducing the electronegativity of the anion site and introducing silver vacancies to optimize the carrier concentration of the Ag6SSeTe material, significantly improving its thermoelectric performance while maintaining the material's excellent mechanical properties and structural stability.
[0046] 2) The present invention provides a silver sulfide-based plastic thermoelectric material, its preparation method, and application. Compared with the traditional melt sintering method, the preparation method can more effectively control the volatilization of sulfur, selenium, and tellurium elements in the material, thereby controlling the elemental composition of the material and improving the preparation repetition rate. The required equipment is simple to operate and has high feasibility.
[0047] 3) The present invention provides a silver sulfide-based plastic thermoelectric material, its preparation method, and application. The concept of the present invention is also applicable to improving the thermoelectric performance of other silver sulfide-based plastic thermoelectric materials, and has the advantages of simplicity, high efficiency, and wide applicability.
[0048] 4) The present invention provides a silver sulfide-based plastic thermoelectric material, its preparation method, and application. The thermoelectric performance of the obtained thermoelectric material is significantly improved while maintaining the sample's good structural stability and plastic deformation ability. The elements required for material preparation are abundant in reserves, low in price, and simple in preparation process, which is conducive to large-scale production and commercial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 Ag in Examples 1 to 5 of the present invention 6-y SSe 1-x Te 1+x Room temperature X-ray diffraction pattern of plastic thermoelectric material.
[0050] Figure 2 The best performance sample in the present invention (Example 5) Ag 5.98 SSe 0.6 Te 1.4 X-ray diffraction pattern at 300-450K.
[0051] Figure 3 The Ag in Examples 1 to 5 and Comparative Example 1 of the present invention is 6-y SSe 1-x Te 1+x Electrical performance analysis diagram of plastic thermoelectric materials, where Figure 3 a, 3c, and 3e are graphs showing the changes in material conductivity, Seebeck coefficient, and power factor with temperature, respectively; Figure 3 b is the graph showing the change of sample carrier concentration and mobility with composition at room temperature; Figure 3d is the variation of Seebeck coefficient of the sample with carrier concentration at room temperature, and the dotted line in the figure is obtained by fitting the SPB model; Figure 3 f is the variation of the power factor of the sample with the carrier concentration at room temperature. The dotted line in the figure is obtained by fitting the SPB model.
[0052] Figure 4 Ag in Examples 1 to 5 of the present invention 6-y SSe 1-x Te 1+x Thermal performance analysis diagram of plastic thermoelectric materials, where Figure 4 a is the relationship between the total thermal conductivity and electrical conductivity of the sample at room temperature. Figure 4 b is the graph of total thermal conductivity of the sample changing with temperature.
[0053] Figure 5 Ag in Examples 1 to 5 of the present invention 6-y SSe 1-x Te 1+x Thermoelectric figure of merit analysis diagram of plastic thermoelectric materials, where Figure 5 a is the graph showing the change of thermoelectric figure of merit of the sample with temperature, Figure 5 b is the room temperature thermoelectric figure of merit of the sample and the Ag2S 1-x Se x and Ag2S 1-x Te x Comparison of room temperature thermoelectric figures of merit of a series of samples.
[0054] Figure 6 The best performance sample in the present invention (Example 5) Ag 5.98 SSe 0.6 Te 1.4 Stress-strain curve under compression condition. DETAILED DESCRIPTION
[0055] The present invention is described in detail below with reference to specific embodiments, but is by no means intended to limit the present invention. Any features, such as preparation methods, materials, structures, or composition ratios, that are not explicitly described in this technical solution are considered to be common technical features disclosed in the prior art.
[0056] The present invention provides a silver sulfide-based plastic thermoelectric material, which is a room temperature high-performance silver sulfide-based plastic thermoelectric material. The chemical formula of the material is Ag 6-y SSe 1-x Te 1+x , where 0 <x<0.50,0≤y<0.03。
[0057] Further, x=0.10, 0.20, 0.30 and 0.40.
[0058] Furthermore, y=0.02.
[0059] Furthermore, x = 0.40 and y = 0.02.
[0060] The present invention provides a method for preparing a silver sulfide-based plastic thermoelectric material, which specifically includes the following steps:
[0061] Step 1: Weighing
[0062] According to the stoichiometric ratio of Ag 6-y SSe 1-x Te 1+x where 0 < x < 0.50 and 0 ≤ y < 0.03, weigh elemental Ag, S, Se, and Te with a total weight of 5 g respectively in an argon glove box;
[0063] Step 2: Ball milling
[0064] In an argon glove box, mix all the elemental substances weighed in Step 1, add ball milling beads, seal them in a ball milling jar, put it into a ball mill, and ball mill for 20 - 30 h under the condition of a rotation speed of 800 - 1000 rpm to obtain flaky Ag 6-y SSe 1-x Te 1+x alloy (alloy sheet);
[0065] Step 3: Cold pressing <000033�>
[0066] Transfer the alloy sheet obtained by ball milling in Step 2 to a stainless steel cold pressing die, add a cold pressing punch, apply pressure up to 50–70 Mpa, and keep the pressure for 20 - 30 min to obtain a dense massive Ag 6-y SSe 1-x Te 1+x alloy (dense massive alloy);
[0067] Step 4: Annealing
[0068] Transfer the dense massive alloy obtained in Step 3 to the cavity of an infrared rapid annealing furnace, evacuate the cavity to vacuum, then heat it up to 200 - 300 °C, keep it warm for 10 - 20 min, and then cool it down to room temperature with the furnace to obtain a high-performance Ag 6-y SSe 1-x Te 1+x plastic thermoelectric material, which is the silver sulfide-based plastic thermoelectric material.
[0069] Furthermore, the ball mill in Step 2 is a high-energy ball mill, the ball milling jar and the ball milling beads are both made of stainless steel, the diameter of the ball milling beads is 10 mm, and the number is 4.
[0070] Furthermore, the rotation speed of the ball mill in Step 2 is 875 rpm and the time is 20 h.
[0071] Furthermore, in step 3, the inner diameter of the cold pressing die is 13 mm, the diameter of the cold pressing punch is 12.7 mm, the pressure applied to the cold pressing punch is 60 MPa, and the holding time is 20 min.
[0072] Furthermore, in step 4, the heating rate of the rapid annealing furnace is 50° C. / min, the annealing holding temperature is 250° C., the annealing holding time is 10 min, and after annealing, the sample is cooled to room temperature in the furnace.
[0073] Based on the existing Ag6SSeTe material, the present invention reduces the electronegativity of the anion position by increasing the Te content in the anion position, introducing more cation vacancies to reduce the number of silver interstitial ions that provide donor energy levels, ultimately achieving the goal of reducing the material's excessive carrier concentration. Furthermore, the introduction of silver vacancies is further performed to obtain the carrier concentration required for optimizing the electrical properties of the Ag6SSeTe material. Simultaneously, the reduction in carrier concentration also effectively reduces the overall thermal conductivity of the Ag6SSeTe material, thereby achieving synergistic optimization of the thermal and electrical properties of the Ag6SSeTe material, and increasing its room-temperature thermoelectric figure of merit by 6 times. Furthermore, the present invention further provides a preparation process that utilizes the material's inherent plasticity to achieve ball milling, cold pressing, and annealing. This process effectively reduces the step of subjecting the sample to high temperatures during the synthesis process, effectively suppressing the volatilization of sulfur, selenium, and tellurium in the material, thereby achieving precise control and high repeatability of the material components during the synthesis process. This has obvious practical significance for materials such as silver sulfide-based plastic thermoelectric materials, whose thermoelectric properties are very sensitive to their components.
[0074] Unless otherwise specified, the experimental reagents and raw materials used in the present invention are commercially available.
[0075] The experimental methods without specific conditions in the following implementations are all based on conventional methods and conditions, or selected according to the product specifications. Unless otherwise specified, the experimental instruments used in the present invention are all conventional laboratory instruments.
[0076] Example 1
[0077] This embodiment provides a silver sulfide-based plastic thermoelectric material, whose chemical formula is Ag6SSeTe.
[0078] In addition, this embodiment also provides a method for preparing the material, and the specific steps are as follows:
[0079] Step 1: Weigh
[0080] In an argon glove box, according to the stoichiometric ratio of Ag6SSeTe, 5 g of Ag, S, Se and Te were calculated and weighed.
[0081] Step 2: Ball Milling
[0082] In an argon glove box, mix the elements weighed in step 1, add four 10 mm diameter stainless steel milling beads, and seal the mixture in a stainless steel milling jar. The jar is then placed in a high-energy ball mill and milled at 875 rpm for 20 h to obtain flaky Ag6SSeTe alloy.
[0083] Step 3: Cold Pressing
[0084] In an argon glove box, 3 g of the flaky Ag6SSeTe alloy obtained by ball milling in Step 2 was weighed and loaded into a stainless steel cold-pressing die with an inner diameter of 13 mm. A stainless steel cold-pressing punch with a diameter of 12.7 mm was then inserted. The filled cold-pressing die was placed on the cold-pressing platform. A pressure of 60 MPa was applied at room temperature and maintained for 20 minutes to obtain a bulk Ag6SSeTe alloy.
[0085] Step 4: Annealing
[0086] The bulk Ag6SSeTe alloy obtained by cold pressing in step 3 above was transferred to a rapid annealing furnace. The furnace chamber was then evacuated to a pressure of 3 Pa and annealed under these conditions: the annealing program had a heating rate of 50°C / min, a holding temperature of 250°C, and a holding time of 10 minutes. After the holding period, the sample was cooled to room temperature in the furnace while the chamber was maintained in vacuum, thereby obtaining the Ag6SSeTe plastic thermoelectric material, namely the silver sulfide-based plastic thermoelectric material.
[0087] Example 2
[0088] This embodiment provides a silver sulfide-based plastic thermoelectric material, whose chemical formula is Ag6SSe 0.8 Te 1.2 .
[0089] In addition, this embodiment also provides a method for preparing the material, and the specific steps are as follows:
[0090] Step 1: Weigh
[0091] In an argon glove box, 0.8 Te 1.2 According to the stoichiometric ratio, calculate and weigh 5g of Ag, S, Se and Te elements.
[0092] Step 2: Ball Milling
[0093] In an argon glove box, the elements weighed in step 1 were mixed and four stainless steel ball milling beads with a diameter of 10 mm were added and sealed in a stainless steel ball milling jar. Subsequently, the ball milling jar was placed in a high-energy ball mill and milled at a speed of 875 rpm for 20 h to obtain flaky Ag6SSe 0.8 Te1.2 alloy.
[0094] Step 3: Cold Pressing
[0095] In an argon glove box, weigh the Ag6SSe flakes obtained by ball milling in step 2 above. 0.8 Te 1.2 Alloy 3g was loaded into a stainless steel cold pressing die with an inner diameter of 13mm, and then a stainless steel cold pressing punch with a diameter of 12.7mm was placed. The loaded cold pressing die was placed on the cold pressing machine platform, and a pressure of 60Mpa was applied at room temperature and maintained for 20 minutes to obtain bulk Ag6SSe 0.8 Te 1.2 alloy.
[0096] Step 4: Annealing
[0097] The bulk Ag6SSe obtained by cold pressing in step 3 above 0.8 Te 1.2 The alloy was transferred to a rapid annealing furnace, and then the furnace chamber was evacuated to a pressure of 3 Pa. Annealing was carried out under these conditions: the annealing program had a heating rate of 50°C / min, a holding temperature of 250°C, and a holding time of 10 minutes. After the holding was completed, the sample was cooled to room temperature in the furnace while the chamber was kept vacuum, and Ag6SSe 0.8 Te 1.2 The plastic thermoelectric material is the silver sulfide-based plastic thermoelectric material.
[0098] Example 3
[0099] This embodiment provides a silver sulfide-based plastic thermoelectric material, whose chemical formula is Ag6SSe 0.7 Te 1.3 .
[0100] In addition, this embodiment also provides a method for preparing the material, and the specific steps are as follows:
[0101] Step 1: Weigh
[0102] In an argon glove box, 0.7 Te 1.3 According to the stoichiometric ratio, calculate and weigh 5g of Ag, S, Se and Te elements.
[0103] Step 2: Ball Milling
[0104] In an argon glove box, the elements weighed in step 1 were mixed and four stainless steel ball milling beads with a diameter of 10 mm were added and sealed in a stainless steel ball milling jar. Subsequently, the ball milling jar was placed in a high-energy ball mill and milled at a speed of 875 rpm for 20 h to obtain flaky Ag6SSe 0.7Te 1.3 alloy.
[0105] Step 3: Cold Pressing
[0106] In an argon glove box, weigh the Ag6SSe flakes obtained by ball milling in step 2 above. 0.7 Te 1.3 Alloy 3g was loaded into a stainless steel cold pressing die with an inner diameter of 13mm, and then a stainless steel cold pressing punch with a diameter of 12.7mm was placed. The loaded cold pressing die was placed on the cold pressing machine platform, and a pressure of 60Mpa was applied at room temperature and maintained for 20 minutes to obtain bulk Ag6SSe 0.7 Te 1.3 alloy.
[0107] Step 4: Annealing
[0108] The bulk Ag6SSe obtained by cold pressing in step 3 above 0.7 Te 1.3 The alloy was transferred to a rapid annealing furnace, and then the furnace chamber was evacuated to a pressure of 3 Pa, and annealing was carried out under this condition. The annealing program had a heating rate of 50°C / min, a holding temperature of 250°C, and a holding time of 10 minutes. After the holding was completed, the sample was cooled to room temperature in the furnace while the chamber was kept vacuum, and Ag6SSe 0.7 Te 1.3 The plastic thermoelectric material is the silver sulfide-based plastic thermoelectric material.
[0109] Example 4
[0110] This embodiment provides a silver sulfide-based plastic thermoelectric material, whose chemical formula is Ag6SSe 0.6 Te 1.4 .
[0111] In addition, this embodiment also provides a method for preparing the material, and the specific steps are as follows:
[0112] Step 1: Weigh
[0113] In an argon glove box, 0.6 Te 1.4 According to the stoichiometric ratio, calculate and weigh 5g of Ag, S, Se and Te elements.
[0114] Step 2: Ball Milling
[0115] In an argon glove box, the elements weighed in step 1 were mixed and four stainless steel ball milling beads with a diameter of 10 mm were added and sealed in a stainless steel ball milling jar. Subsequently, the ball milling jar was placed in a high-energy ball mill and milled at a speed of 875 rpm for 20 h to obtain flaky Ag6SSe0.6 Te 1.4 alloy.
[0116] Step 3: Cold Pressing
[0117] In an argon glove box, weigh the Ag6SSe flakes obtained by ball milling in step 2 above. 0.6 Te 1.4 Alloy 3g was loaded into a stainless steel cold pressing die with an inner diameter of 13mm, and then a stainless steel cold pressing punch with a diameter of 12.7mm was placed. The loaded cold pressing die was placed on the cold pressing machine platform, and a pressure of 60Mpa was applied at room temperature and maintained for 20 minutes to obtain bulk Ag6SSe 0.6 Te 1.4 alloy.
[0118] Step 4: Annealing
[0119] The bulk Ag6SSe obtained by cold pressing in step 3 above 0.6 Te 1.4 The alloy was transferred to a rapid annealing furnace, and then the furnace chamber was evacuated to a pressure of 3 Pa, and annealing was carried out under this condition. The annealing program had a heating rate of 50°C / min, a holding temperature of 250°C, and a holding time of 10 minutes. After the holding was completed, the sample was cooled to room temperature in the furnace while the chamber was kept vacuum, and Ag6SSe 0.6 Te 1.4 The plastic thermoelectric material is the silver sulfide-based plastic thermoelectric material.
[0120] Example 5
[0121] This embodiment provides a high-performance silver sulfide-based plastic thermoelectric material that is substantially the same as that in embodiment 4, except that:
[0122] This embodiment further introduces silver vacancies on the basis of embodiment 4 to achieve the optimization of material carrier concentration. Its chemical formula is Ag 5.98 SSe 0.6 Te 1.4 .
[0123] In addition, this embodiment also provides a method for preparing the material, and the specific steps are as follows:
[0124] Step 1: Weigh
[0125] In an argon glove box, 5.98 SSe 0.6 Te 1.4 According to the stoichiometric ratio, calculate and weigh 5g of Ag, S, Se and Te elements.
[0126] Step 2: Ball Milling
[0127] In an argon glove box, the elements weighed in step 1 were mixed and four stainless steel ball milling beads with a diameter of 10 mm were added and sealed in a stainless steel ball milling jar. Subsequently, the ball milling jar was placed in a high-energy ball mill and milled at a speed of 875 rpm for 20 h to obtain flaky Ag. 5.98 SSe 0.6 Te 1.4 alloy.
[0128] Step 3: Cold Pressing
[0129] In an argon glove box, weigh the Ag flakes obtained by ball milling in step 2 above. 5.98 SSe 0.6 Te 1.4 Alloy 3g was loaded into a stainless steel cold pressing die with an inner diameter of 13mm, and then a stainless steel cold pressing punch with a diameter of 12.7mm was placed. The loaded cold pressing die was placed on the cold pressing machine platform, and a pressure of 60Mpa was applied and maintained for 20 minutes to obtain blocky Ag. 5.98 SSe 0.6 Te 1.4 alloy.
[0130] Step 4: Annealing
[0131] The bulk Ag obtained by cold pressing in step 3 above 5.98 SSe 0.6 Te 1.4 The alloy was transferred to a rapid annealing furnace, and then the furnace chamber was evacuated to a pressure of 3 Pa. Under this condition, annealing was carried out: the annealing program had a heating rate of 50°C / min, a holding temperature of 250°C, and a holding time of 10 minutes. After the holding was completed, the sample was cooled to room temperature in the furnace while the chamber was kept vacuum, and Ag was obtained. 5.98 SSe 0.6 Te 1.4 The plastic thermoelectric material is the silver sulfide-based plastic thermoelectric material.
[0132] Comparative Example 1
[0133] This comparative example is a silver sulfide-based plastic thermoelectric material whose performance is optimized by combining entropy engineering with the introduction of silver vacancies in the prior art. Its chemical formula is Ag 2-σ S 1-2x Se x Te x, where x = 0.13, 0.15, 0.20 and 0.33, σ = 0.01 and 0.02. The specific preparation method is described in the paper "Chang, Yi, et al. "Room-temperature cubic Ag2S1-2xSexTex with promising ductility and thermoelectric properties enabled byentropy engineering." Advanced Functional Materials 34.12(2024):2310016."
[0134] Comparative Example 2
[0135] This comparative example is a silver sulfide-based plastic thermoelectric material in the prior art that optimizes the performance of silver sulfide by solid-dissolving selenium and tellurium elements in the sulfur position. Its chemical formulas are Ag2S 1-x Se x (where x = 0.3 and 0.5) and Ag2S 1-x Te x (where x = 0.2, 0.3, 0.5, and 0.6). The specific preparation method is described in the paper “Wei, Tian-Ran, et al. “Ag2Q-based (Q = S, Se, Te) silver chalcogenide thermoelectric materials.” Advanced Materials 35.1(2023):2110236.”
[0136] Then, Examples 1-5 and Comparative Examples 1-2 were tested and analyzed:
[0137] (1) The plastic thermoelectric materials prepared in Examples 1–5 were characterized using a Rigaku SmartLab-Ⅱ X-ray diffractometer. The samples used were annealed bulk samples, and the X-ray source was Cu-K α , X-ray diffraction results at room temperature are as follows Figure 1 Further, under the temperature variation condition of 300–450K, the temperature variation X-ray diffraction results of the sample with the best thermoelectric performance (Example 5) are as follows: Figure 2 As shown, the temperature control stage used is Anton paar-TTK-600, and the environment is a vacuum environment (3 Pa).
[0138] (2) The electrical properties of the plastic thermoelectric materials prepared in Examples 1-5 were characterized using a commercial ULVAC-RIKO-ZEM 3 device. The test conditions were a helium environment, and the results were the electrical conductivity and Seebeck coefficient of the samples. Subsequently, the power factor was calculated using the formula Powerfactor = S 2 The power factor is calculated by σ. The results are as follows Figure 3 a, 3c and 3e.
[0139] (3) Quantum Design-PPMS was used to characterize the room temperature carrier concentration and mobility of the plastic thermoelectric materials prepared in Examples 1-5. The results are as follows: Figure 3 As shown in b.
[0140] (4) Matlab calculation software was used to calculate the Ag content in Example 5 based on the SPB model. 5.98 SSe 0.6 Te 1.4 The variation of Seebeck coefficient and power factor of the material with carrier concentration at room temperature is shown as follows: Figure 3 d and dashed lines in 3f.
[0141] (5) The thermal diffusion coefficient D of the plastic thermoelectric material prepared in the above examples 1-5 was characterized using NETZSCH-LFA 457. Then, the thermal conductivity was calculated according to the formula κ=DC p ρ is calculated to obtain the thermal conductivity of the material. P is the heat capacity of the material, estimated according to the Dulong-Petit law, and ρ is the material density, measured according to the Archimedean drainage method. Figure 4 As shown in b.
[0142] (6) The thermoelectric merit of the material is calculated according to the thermoelectric merit formula zT = S 2 σT / κ is calculated, where S is the Seebeck coefficient of the material, σ is the electrical conductivity of the material, T is the absolute temperature of the test environment, and κ is the total thermal conductivity of the material. The results are as follows: Figure 5 As shown in a.
[0143] (7) The stress-strain curves of Examples 4 and 5 under compression conditions were measured using a LiShi Instrument-LD23 microcomputer-controlled electric universal tester. The results are as follows: Figure 6 shown.
[0144] like Figure 1As shown, during the process of reducing the electronegativity of the anion positions in the Ag6SSeTe material (increasing the content of Te element) and introducing silver vacancies, the plastic thermoelectric materials prepared in Examples 1-5 can all maintain the intermediate-temperature cubic phase structure of Ag2S, indicating that while optimizing the performance, the present invention can maintain the stability of the original sample phase structure, and thus maintain the original plastic mechanical properties of the sample. However, it should be noted that as the content of Te element increases and the content of introduced silver vacancies increases, characteristic diffraction peaks of the Ag2Te second phase can be observed in the X-ray diffraction spectrum of the sample between 2θ angles of 40°–45°. The appearance of the Ag2Te second phase will cause Ag 6-y SSe 1-x Te 1+x the material composition to deviate from the original design, thereby reducing the thermoelectric performance and stability of the material. Therefore, in the Ag 6-y SSe 1-x Te 1+x material, both the content of Te element and the content of introduced silver vacancies have preferred amounts, and the preferred amounts are 0 < x < 0.5 and 0 < y < 0.03. Further, as Figure 2 shown, the cubic phase structure of the sample in Example 5 can remain stable in the temperature range of 300 - 450K, indicating that the high-performance plastic thermoelectric material (Ag 6-y SSe 1-x Te 1+x ) prepared by the present invention has good structural thermal stability and will not undergo structural mutations during the actual application of temperature difference, thereby maintaining performance stability.
[0145] As Figure 3 shown in b, by reducing the electronegativity of the anion positions in the Ag6SSeTe material (increasing the content of Te element) and further introducing silver vacancies, the room-temperature carrier concentration of the samples in Examples 1-5 gradually decreases. Correspondingly, as Figure 3 shown in c, the absolute value of the room-temperature Seebeck coefficient of the sample shows a gradually increasing trend with the increase of the x value, and is significantly improved in Example 5, and further shows an increasing trend with the increase of temperature. Benefiting from the increase in the absolute value of the Seebeck coefficient, the power factor of the samples in Examples 1-5 increases significantly in the entire measurement temperature range (300 - 450K) ( Figure 3 e). By comparing with Comparative Example 1 ( Figure 3 d and 3f), it can be found that the present invention is beneficial to reducing the carrier concentration of the material to a lower value, thereby obtaining a larger absolute value of the Seebeck coefficient, and further improving the power factor of the material. At the same time, the lower carrier concentration significantly reduces the electrical conductivity of the material while optimizing the power factor ( Figure 3 a), which is beneficial to reducing the contribution of electron thermal conductivity to the total thermal conductivity of the material, and thus reducing the total thermal conductivity of the material, and achieving the synergistic optimization of the thermal and electrical properties of the material.
[0146] like Figure 4 As shown in a, benefiting from the reduction in conductivity caused by the reduction in carrier concentration in the materials of Examples 1-5, the total thermal conductivity of the materials at room temperature shows a linear downward trend with the conductivity. 6-y SSe 1-x Te 1+x For this type of fast ion conductor, the total thermal conductivity of the material is not sensitive to temperature changes and hardly changes with temperature. Figure 4 Under the different temperature conditions in b, the total thermal conductivity of the materials in Examples 1-5 changes in the same manner as at room temperature, and shows a significant downward trend with the increase of the x value.
[0147] like Figure 5 As shown in Figure a, benefiting from the synergistic optimization of thermal and electrical properties caused by the optimization of carrier concentration in the materials of Examples 1-5, the room temperature thermoelectric figure of merit of the material is significantly improved from 0.1 in Example 1 to 0.65 in Example 5, and shows a significant upward trend as the test temperature increases. Figure 5 As shown in b, compared with the silver sulfide-based plastic thermoelectric material with performance optimization based on Ag2S in the prior art in Comparative Example 2, the room temperature thermoelectric figure of merit of Example 5 is currently the best.
[0148] like Figure 6 As shown, under the condition of vertical compression, the compressive strain of the sample in Example 5 can reach 45%, showing good plastic deformation ability, which is conducive to the simple processing of thermoelectric materials and the conformity to the curved heat source surface.
[0149] In summary, the synergistic scheme of reducing the electronegativity of anion positions and introducing silver vacancies adopted in the present invention can effectively reduce the carrier concentration of Ag6SSeTe, a silver sulfide-based plastic thermoelectric material, thereby achieving synergistic optimization of its thermal and electrical properties. 5.98 SSe 0.6 Te 1.4 The room-temperature thermoelectric figure of merit of the plastic thermoelectric material reached 0.65, nearly six times higher than the initial sample. The material also exhibited excellent plastic mechanical properties and structural stability. Furthermore, the preparation method of ball milling, cold pressing, and annealing provided by the present invention exhibited the advantages of simplicity, speed, and efficiency.
[0150] The above description of the embodiments is intended to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above-described embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention, without departing from the scope of the present invention, should be within the scope of protection of the present invention.
Claims
1. A silver sulfide-based plastic thermoelectric material, characterized in that: The structural chemical formula of the silver sulfide-based plastic thermoelectric material is Ag 6-y SSe 1-x Te 1+x , where 0 <x<0.50,0≤y<0.03。 2. The silver sulfide-based plastic thermoelectric material according to claim 1, characterized in that: x=0.10、0.20、0.30、0.40。 3. The silver sulfide-based plastic thermoelectric material according to claim 1, characterized in that: x=0.40, y=0.
02.
4. The silver sulfide-based plastic thermoelectric material according to claim 3, characterized in that: The cubic phase structure of the silver sulfide-based plastic thermoelectric material remains stable within the temperature range of 300-450K; The room temperature thermoelectric figure of merit of the silver sulfide-based plastic thermoelectric material is 0.60 to 0.70; Under vertical compression, the compressive strain of the silver sulfide-based plastic thermoelectric material is 40-50%.
5. A method for preparing a silver sulfide-based plastic thermoelectric material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Step 1: Weigh elemental Ag, elemental S, elemental Se, and elemental Te according to the stoichiometric ratio of Ag 6-y SSe 1-x Te 1+x where 0 < x < 0.50 and 0 ≤ y < 0.03, respectively. Step 2: Mix the Ag, S, Se and Te weighed in step 1 and ball mill them to obtain Ag flakes. 6- y SSe 1-x Te 1+x alloy; Step 3: Ball mill the Ag flakes obtained in step 2 6-y SSe 1-x Te 1+x The alloy is cold pressed to obtain dense block Ag 6- y SSe 1-x Te 1+x alloy; Step 4: The dense bulk Ag obtained in step 3 6-y SSe 1-x Te 1+x The alloy is annealed in vacuum to obtain Ag 6- y SSe 1-x Te 1+x The plastic thermoelectric material is the silver sulfide-based plastic thermoelectric material.
6. The method for preparing the silver sulfide-based plastic thermoelectric material according to claim 5, characterized in that: In step 1, Ag, S, Se, and Te are weighed separately under an inert atmosphere.
7. The method for preparing the silver sulfide-based plastic thermoelectric material according to claim 5, characterized in that: In step 2, the mixing and ball milling process is carried out under an inert atmosphere; In step 2, the ball milling specifically includes the following process: adding ball milling beads, sealing the ball milling jar, placing the ball mill in a ball mill for ball milling at a rotation speed of 800-1000 rpm for 20-30 hours; The ball mill is a high-energy ball mill. The ball mill jar and ball mill beads are made of stainless steel. The diameter of the ball mill beads is 8-15 mm, and the number of the ball mill beads is 3-10.
8. The method for preparing the silver sulfide-based plastic thermoelectric material according to claim 5, characterized in that: Step 3 specifically includes the following process: The Ag flakes obtained by ball milling in step 2 6-y SSe 1-x Te 1+x The alloy is transferred to a cold pressing die, a cold pressing punch is added, and the pressure is increased to 50-70 MPa. The pressure is maintained at room temperature for 20-30 minutes to obtain a dense block of Ag. 6-y SSe 1-x Te 1+x alloy; In step 3, the cold pressing mold is a stainless steel cold pressing mold, the inner diameter of the cold pressing mold is 8-15 mm, and the diameter of the cold pressing punch is 7.7-14.7 mm.
9. The method for preparing the silver sulfide-based plastic thermoelectric material according to claim 8, characterized in that: Step 4 specifically includes the following process: The dense bulk Ag obtained in step 3 6-y SSe 1-x Te 1+x The alloy was transferred to the infrared rapid annealing furnace cavity, and the infrared rapid annealing furnace cavity was evacuated to a vacuum of 3-5 Pa. The temperature was then raised to 200-300 ° C, kept at this temperature for 10-20 minutes, and then cooled to room temperature in the infrared rapid annealing furnace to obtain Ag. 6-y SSe 1-x Te 1+x The plastic thermoelectric material is the silver sulfide-based plastic thermoelectric material.
10. An application of the silver sulfide-based plastic thermoelectric material according to any one of claims 1 to 4, characterized in that: The silver sulfide-based plastic thermoelectric material is used to power room-temperature flexible electronic devices.